أثر الحوافز على أداء الموارد البشرية وولائها الوظيفي دراسة تطبيقية على شركة تغليف للصناعات منطقة صحار الصناعية بسلطنة عمان - ميًا, علي; ديب, كنده علي; القاسمي, صالح بن ناصر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
حظيت الحوافز وما زالت باهتمام علماء السلوك الإنساني والإداري باعتبارها متغيرات مستقلة للدافعية تركز على إطلاق وتحرير طاقات العاملين ليكونوا أكثر كفاءة وإنتاجية وأعلى أداء. وتقوم عملية التحفيز باستخدام المحفزات على مفهوم إثارة وتوجيه الأفراد العاملين لأداء أعمالهم بشكل أفضل، وقد تركز بحثنا على دراسة نظام الحوافز المعمول به حالياً في شركة " تغليف للصناعات ( محل الدراسة )" المنتجة لأفلام البولي بروبلين بمنطقة صحار الصناعية بسلطنة عمان، ومعرفة الحوافز الأخرى التي يرغب العاملون للحصول عليها أيضاً، واختبار تأثير نظام الحوافز في المؤسسة على الولاء الوظيفي، ومعدلات الإنتاج من وجهة نظر العاملين والرؤساء. ولقد توصلت الدراسة إلى وجود علاقة ذي دلالة معنوية بين فاعلية نظام الحوافز والولاء الوظيفي بالإضافة إلى وجود علاقة بين نظام الحوافز ومعدلات الإنتاج. Incentives has received continuous attention from humanitarian and administrative scientists as they are considered private variables for motivation that focuses on launching and releasing the workers' energy to be more efficient and productive . The stimulating process using incentives is based on the concept of provoking and guiding workers to perform better. This thesis studies the incentive system used in "Taghleef Industries Company (the study area)" which produces polypropylene at Sohar Industrial Area in Sultanate of Oman. It also tries to know other incentives workers would like to get too, and tests the effect of the incentives system in the institution on the Job loyalty and the production rates from the point of view of both workers and bosses. The Research has concluded the existence of a relation between the efficiency of incentives system and loyalty in addition to the existence of a relation between that system and the production rates.